The sorority murder - Brennan, Allison (Mira, 2021)
Lucas Vega is obsessed with the murder of Candace Swain three years after her death, and while interning at the medical examiner's, he discovers new information and teams up with a former U.S. marshal who not only exposes Candace's secret life but also Lucas's to solve this case.